Respostas

2014-08-07T16:08:44-03:00
A) -3x +10 = 2x + 8 + 1
- 3x - 2x = + 8 + 1 - 10
- 5x = 9 - 10
- 5x = - 1 (-1)
5x = 1
x = 1/5

b) 5x - 5 + x = 9 + x
5x + x - x = 9 + 5
5x = 14
x = 14/5

c) 7x (?) 4 - 4x= - 2x + 8 - 3x
Está faltando um sinal.

d) -x - 5 + 4x = -7x + 6x + 15
-x + 4x + 7x - 6x = 15 + 5
4x + 7x - 6x - x = 20
4x + 7x - 7x = 20
4x = 20
x = 20/4
x = 5

e) 3x - 2x = 3x + 2
3x - 2x - 3x = 2
- 2x = 2 (-1)
2x = - 2
x = -2/2
x = -1

f) 2 - 4x = 32 - 18x + 12
- 4x + 18x = 32 + 12 - 2
14x = 42
x = 42/14
x = 3

g) 2x - 1 = -3 + x + 4
2x - x = -3 + 4 + 1
x = 2

h) 3x - 2 - 2x - 3 = 0
3x - 2x = + 2 + 3
x = 5

i) 10 - 9x + 2x = 2 - 3x
- 9x + 2x + 3x = 2 - 10
- 9x + 5x = -8
- 4x = - 8 (-1)
4x = 8
x = 8/4
x = 2

j) 4x - 4 - 5x = 6 + 900
4x - 5x = 906 + 4
- x = 910 (-1)
x = - 910

k) 2 - 3x = 2x + 12 - 3x
- 3x - 2x + 3x = 12 - 2
- 2x = 10 (-1)
2x = - 10
x = -10/2
x = -5

1 5 1